Dismantling founder's syndrome - Kislenko, S (The Philanthropist, 2022)
Founder’s syndrome is widely whispered about in the non-profit sector but rarely analyzed or dismantled. Contributor Susanna Kislenko has been studying the phenomenon for years and offers some insight.